Peran Taman Bacaan Masyarakat (TBM) Sudut Baca Soreang dalam Meningkatkan Minat Baca Masyarakat di Kabupaten Bandung - Abdul Holik (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2013)
With creativity owned public library (TBM) Sudut Baca Soreang, public libraries during this type of rigid and mute seem capable known to the public with a more familiar and friendly. Place refresentatif reading, reading room fresh color, flexible rules have provided flexibility to the public in accessing information in its own way. So it is not strange, if the number of visits in the public library is increasingly rising. This indicates that the library is not a place for those people nerds and stiff but places for all those who want to increase knowledge and insights. These conditions provide an opportunity for the Government to adopt a management model that is made for the purpose of SBS TBM Government in improving the intelligence community can be realized as mandated by Law.